Maturation arrest of human oocytes at germinal vesicle stage - Zhi Qin Chen; Teng Xiao Ming; Hans Ingolf Nielsen (Wolters Kluwer Medknow Publications, 2010)
Maturation arrest of human oocytes may occur at various stages of the cell cycle. A total failure of human oocytes to complete meiosis is rarely observed during assisted conception cycles. We describe here a case of infertile couples for whom all oocytes repeatedly failed to mature at germinal vesicle (GV) stage during in vitro fertilization/Intra cytoplasmic sperm injection (IVF/ICSI). The patient underwent controlled ovarian stimulation followed by oocyte retrieval and IVF/ICSI. The oocytes were stripped off cumulus cells prior to the ICSI procedure and their maturity status was defined. The oocyte maturation was repeatedly arrested at the GV. Oocyte maturation arrest may be the cause of infertility in this couple. The recognition of oocyte maturation arrest as a specific medical condition may contribute to the characterization of the currently known as "oocyte factor." The cellular and genetic mechanisms causing oocyte maturation arrest should be the subject for further investigation.